Pelatihan Elektronika Dasar Bagi Siswa Sekolah Menengah Atas di Wilayah Kalimantan Barat - rahman, syaifur (Universitas Tanjungpura, 2021)
The community service in the form of electronics training aims to introduce the field of electronics to high school students in several districts in West Kalimantan.This electronics training is carried out to increase the knowledge of students in the field of electronics to increase their interest in studying at the Department of Electrical Engineering,Tanjungpura University.There are five schools targeted for the training, namely: MAN IC Sambas, SMKN 1 Sambas, SMAN 1 Siantan, SMAN 1 Paloh Sambas and SMKN 1 Mandor Landak.The method used is class discussion and practice by directly involving students to jointly assemble electronic circuits using electronic modules that have been made.During the training activities the students were very enthusiastic about participating in the training and this was shown by many students who wanted to try assembling electronic circuits with the provided electronic modules.Furthermore, the electronic modules were handed over to the school in order to motivate students to try to learn other electronic circuits.